NixMnyCozO Nanowire/CNT Composite Microspheres with 3D Interconnected Conductive Network Structure via Spray‐Drying Method: A High‐Capacity and Long‐Cycle‐Life Anode Material for Lithium‐Ion Batteries. Issue 15 (12th March 2019) - Li, Qing; Zhu, Guozhen; Zhao, Yunhao; Pei, Ke; Che, Renchao
Abstract: The combination of high‐capacity and long‐term cycling stability is an important factor for practical application of anode materials for lithium‐ion batteries. Herein, Ni x Mn y Co z O nanowire ( x + y + z = 1)/carbon nanotube (CNT) composite microspheres with a 3D interconnected conductive network structure (3DICN‐NCS) are prepared via a spray‐drying method. The 3D interconnected conductive network structure can facilitate the penetration of electrolyte into the microspheres and provide excellent connectivity for rapid Li + ion/electron transfer in the microspheres, thus greatly reducing the concentration polarization in the electrode. Additionally, the empty spaces among the nanowires in the network accommodate microsphere volume expansion associated with Li + intercalation during the cycling process, which improves the cycling stability of the electrode. The CNTs distribute uniformly in the microspheres, which act as conductive frameworks to greatly improve the electrical conductivity of the microspheres. As expected, the prepared 3DICN‐NCS demonstrates excellent electrochemical performance, showing a high capacity of 1277 mAh g −1 at 1 A g −1 after 2000 cycles and 790 mAh g −1 at 5 A g −1 after 1000 cycles. This work demonstrates a universal method to construct a 3D interconnected conductive network structure for anode materials Abstract : A Ni x Mn y Co z O ( x + y + z = 1) nanowire/carbon nanotube (CNT) composite with microspherical morphology and a 3D interconnected conductive network structure is synthesized via a spray‐drying method, and demonstrates excellent electrochemical performance. After 1000 cycles at 5 A g −1, its discharge capacity is maintained at 790 mAh g −1 . This work demonstrates a universal method to construct a 3D conductive network for anode materials.